DIAGNOSTIC ACCURACY OF CONTRAST ENHANCED COMPUTED TOMOGRAPHY IN STAGING OF COLORECTAL CARCINOMA: Contrast Enhanced Computed Tomography - Sultana, Nasira; Khan, Sumayya; Baloch, Salah Ud Din (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the diagnostic accuracy of CT scan in staging of colorectal carcinoma among biopsy proven patients of colorectal carcinoma by taking histopathological finding as gold standard. Study Design: Cross-sectional validation study. Place and Duration of Study: Combined Military Hospital Rawalpindi, Six months, from Jul 2015 to Dec 2015. Material and Methods: A total of 176 cases of 15-70 years of age, diagnosed of colorectal carcinoma oncolonoscopic biopsy, were included in the study. Patients with previous malignancies other than colorectal carcinoma, allergy to the contrast agent and pregnant patients were excluded from the study. All the patients then underwent CT scan for detection of the stage of cancer. After surgery, histopathology of the resected specimen was compared with the findings on CT scan. Results: Mean age was 50.27 ± 14.50 years. Out of these 176 patients, 113 (64.20%) were male and 63 (35.80%) were females with ratio of 1.8:1. Among CT positive, 80 were true positive while 11 were false positive. Among, CT negative patients, 12 were false negative while 73 were true negative. Overall sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of CT in staging colorectal carcinoma taking histopathology as gold standard was 87.91%, 85.88%, 86.96%, 86.90% and 86.93% respectively. Conclusion: This study concluded that CT scan is a highly sensitive and accurate modality for pre-operative detection of stage of colorectal carcinoma.